Structure Design of Cathode Electrodes for Solid‐State Batteries: Challenges and Progress. Issue 3 (1st October 2020) - Zhang, Xu-Dong; Yue, Feng-Shu; Liang, Jia-Yan; Shi, Ji-Lei; Li, Hong; Guo, Yu-Guo
Abstract : Solid‐state lithium batteries have aroused wide interest with the probability to guarantee safety and high energy density at the same time. In the past decade, fruitful endeavors have been devoted to promoting each component of these batteries, including solid electrolyte with high conductivity, dendrite‐free lithium anode, and high‐capacity cathode. However, the currently achieved cell performances are still inconsistent with the original expectations, in which interfaces severely hamper the energy output and cycling stability for practical application. Herein, particular attentions are paid to the interface between cathode and solid electrolyte. The huge resistance caused at this interface can be found throughout the entire life of batteries from preparation to operation. Accordingly, these issues are divided into physical contact, thermal interdiffusion, space‐charge layer, electrochemomechanical breakdown, and undesirable side reactions and further elucidated in detail. Moreover, representative developments concerning the cathode/solid electrolyte interface in terms of compositional and morphological control in cathode, architecture and manufacture design in solid electrolyte, and artificial interphase building are summarized. With these efforts, the emphasis of the fundamental issues and perspectives of interface between cathode and solid electrolyte may eventually contribute to high‐energy long‐cycling solid‐state lithium batteries. Abstract : Solid‐state lithium batteries, though promising, still face huge resistance at the electrode/solid electrolyte interface obstructing their available performance. Through summarizing observations at the cathode side, the limiting factors can be divided into five parts according to the involved properties and emerging stage during battery processing. Rational designs based on these fundamentals are highly expected for commercialization of solid‐state batteries.